INSTILLING CHRISTIAN VALUES FOR CHILDREN WITH DISABILITIES AT PERMATA SENTANI CHRISTIAN KINDERGARTEN - Ivone Sole Babys; Septiyani Endang Yunitasari; Ariati; Florence A. Boray; Konny F. Daisiu; Sintje Sbortje Ogobue (International Conferences on Early Childhood Education Proceedings, 2023)
The problem in the study is that children with hearing impairment who always explode their emotions if what they want is not obtained, shout, cry suddenly or hit friends and teachers. Research was conducted to find out how the influence of instilling Christian values in children with disabilities. This research is a qualitative descriptive field research to describe the process of instilling Christian values for children with disabilities in Permata Christian Kindergarten. The handling of children with hearing impairment in Permata Christian Kindergarten is carried out by instilling Christian values (character) to children, teachers make themselves examples and role models for children and create a comfortable environment for children (teachers and other children always say positive words) so that with such an approach children do not feel themselves different from other children but feel accepted in their environment which is marked by a change in attitude in children with hearing impairment both emotionally and socially